Approaching Suharto's Indonesia from the margins - Shiraishi, Takashi, 1950- (Translation series (Cornell University. Southeast Asia Program) ;, 1994)
This text is the fourth and final volume in a series of essays by Japanese scholars of Southeast Asia. The authors examine issues such as the political styles and methodologies of Suharto's New Order government, the economic development of Indonesia under Suharto, and the economic and cultural relationship between Japan and Indonesia.